The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jvh.12563
|View full text |Cite
|
Sign up to set email alerts
|

The gamma‐glutamyl transpeptidase‐to‐platelet ratio predicts liver fibrosis and cirrhosis in HBeAg‐positive chronic HBV infection patients with high HBV DNA and normal or mildly elevated alanine transaminase levels in China

Abstract: The gamma-glutamyl transpeptidase-to-platelet ratio (GPR) is a new serum diagnostic model, which is reported to be more accurate than aspartate transaminase-to-platelet ratio index (APRI) and fibrosis index based on the four factors (Fib-4) for the diagnosis of significant fibrosis and cirrhosis in chronic HBV infection (CHBVI) patients in West Africa. To evaluate the performance of the GPR model for the diagnosis of liver fibrosis and cirrhosis in HBeAg-positive CHBVI patients with high HBV DNA (≥5 log copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 23 publications
2
37
2
Order By: Relevance
“…The problem goes to how we identify this subgroup of CHB patients accurately without liver biopsy. APRI and GPR have been proposed to evaluate hepatic fibrosis accurately in CHB patients . In addition, our multivariate analysis revealed that AST and GGT were independent factors of advanced fibrosis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The problem goes to how we identify this subgroup of CHB patients accurately without liver biopsy. APRI and GPR have been proposed to evaluate hepatic fibrosis accurately in CHB patients . In addition, our multivariate analysis revealed that AST and GGT were independent factors of advanced fibrosis.…”
Section: Discussionmentioning
confidence: 69%
“…and Li et al. in which GPR not only yielded good AUROC for predicting fibrosis but showed better performance as compared with APRI in Gambian and Chinese CHB cohorts . As GPR had a high NPV for the prediction of no advanced fibrosis at the cut‐off value of 0.17, we categorized patients with GPR <0.17 into the subgroup of low‐grade fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We found only Lemoine et al's study (11) to be similar to our study. It was conducted mainly in patients who were negative for HBeAg, while other studies enrolled all positive (21) or both patients (20,27,29,30). Another point is that most previous studies were conducted in China but our study and the study by Lemoine et al (11) were conducted in Africa.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, the identification of patients with PNALT who still suffer from severe liver injury is challenging. Recently, indirect serum markers such as the FIB-4 index, APRI and GPR, which affect the ALT level and other serum parameters, have been proposed as clinical markers in routine laboratory measurements to predict the severity of liver damage [11, 18]. …”
Section: Discussionmentioning
confidence: 99%